Pengaruh Layanan Konseling Individual terhadap Kepercayaan Diri Warga Binaan di Lembaga Pemasyarakatan Klas II B Lubuk Basung - Yani, Susi Endri; Santosa, Budi (Lembaga Yasin AlSys, 2023)
This research departs from the phenomenon that there are inmates or commonly referred to as prison inmates who have a low level of self-confidence compared to others, where inmates feel embarrassed to interact, there is past trauma and negative thoughts that are more prominent in them. These negative thoughts are often experienced by individuals who experience problems with low self-esteem. Individuals think that they are different from other people, causing them to feel inferior in socializing. The goal to be achieved in this study is to determine whether there are significant differences before and after being given individual counseling to increase the confidence of prisoners in Class II B Penitentiary in Lubuk Basung. This research is a pre-experimental research model of One Group Pre-test Post-test Design. The population is Class II B Penitentiary Prisoners of Lubuk Basung while the research sample is inmates ranging in age from 20 to 35 years as many as 5 inmates who are indicated to have a low level of self-confidence based on non-random sampling techniques and recommendations from prison staff. The data collection instrument is a Likert scale. Data analysis techniques used non-parametric statistical tests using the Wilcoxon rack test, hypothesis testing using the Z test (Wilcoxon) with the help of Statistical Product and Service Solution (SPSS) version 24. The results of research that have been known from the results of the Z test (Wilcoxon) show the difference between the pre-test and post-test scores. From the results of the calculation of the Wilcoxon test, a significant value of 0.043 was obtained. Based on the applicable provisions, it is known that the results of the Wilcoxon Asymp.Sig test. (2-tailed) < α (α = 0.05) which means that Ha is accepted and Ho is rejected. From the results of the calculation of the Wilcoxon test, it can be concluded that self-confidence increases after being given treatment, namely individual counseling.